Yaw moment control for vehicle stability in a crosswind. (22nd December 2005) - Boada, B.L.; Boada, M.J.L.; Diaz, V.
Owing to the effect of wind disturbance on its behaviour, a vehicle may not follow the desired trajectory. This paper presents a new yaw moment control based on fuzzy logic to improve vehicle handling and stability in a crosswind. The main advantages of fuzzy methods are their simplicity and their good performance to control non-linear systems. The developed controller generates a suitable yaw moment, which is obtained from the difference of the brake forces between the front wheels so that the vehicle follows the target values of the yaw rate and the sideslip angle. Simulation results show the effectiveness of the proposed control method when the vehicle is subjected to driving conditions (dry road surface and snow) and wind disturbance.